2016
DOI: 10.1093/nar/gkw1124
|View full text |Cite
|
Sign up to set email alerts
|

Structures of human SRP72 complexes provide insights into SRP RNA remodeling and ribosome interaction

Abstract: Co-translational protein targeting and membrane protein insertion is a fundamental process and depends on the signal recognition particle (SRP). In mammals, SRP is composed of the SRP RNA crucial for SRP assembly and function and six proteins. The two largest proteins SRP68 and SRP72 form a heterodimer and bind to a regulatory site of the SRP RNA. Despite their essential roles in the SRP pathway, structural information has been available only for the SRP68 RNA-binding domain (RBD). Here we present the crystal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 63 publications
(102 reference statements)
1
39
0
Order By: Relevance
“…Herein, we solved the first SRP68/72 complex structure at atomic resolution (1.7 Å). In the final phase of manuscript submission, a similar structure of a SRP68/72 complex was reported ( Becker et al, 2017 ). In our study, we identified the minimal domains of both SRP68 and SRP72 that are necessary and sufficient for their interaction, and found a C-terminal capping helix in SRP72 that is required for tight binding.…”
Section: Discussionmentioning
confidence: 69%
“…Herein, we solved the first SRP68/72 complex structure at atomic resolution (1.7 Å). In the final phase of manuscript submission, a similar structure of a SRP68/72 complex was reported ( Becker et al, 2017 ). In our study, we identified the minimal domains of both SRP68 and SRP72 that are necessary and sufficient for their interaction, and found a C-terminal capping helix in SRP72 that is required for tight binding.…”
Section: Discussionmentioning
confidence: 69%
“…Similarly, NUP98 can also be utilized for viral entry into the nucleus. Additional three CSPs in this category, RPL36 and RPS20 40, 60 as well as SRP72 61 , could be employed for viral transcription and protein synthesis (Fig. 3e).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial complexes of the closed state depicted an NG heterodimer detached from the SRP RNA tetraloop in which the distal region of the SRP RNA could not be fully visualized due to flexibility918. Previous cryo-EM studies on the eukaryotic SRP–SR complex revealed an additional density at the SRP distal region19 that was recently interpreted by docking a crystal structure of the eukaryotic NG heterodimer into this density202122.…”
mentioning
confidence: 99%